2002
DOI: 10.1007/s00520-002-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in young adult survivors of childhood cancer

Abstract: In recent years the necessity of measuring quality of life in childhood cancer survivors has been stressed. This paper gives an overview of the results of studies into the quality of life (QL) of young adult survivors of childhood cancer and suggest areas for future research. The review located 30 empirical studies published up to 2001. The results are described in terms of the following QL dimensions: physical functioning (QL, general health), psychological functioning (overall emotional functioning, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
265
7
21

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(319 citation statements)
references
References 42 publications
26
265
7
21
Order By: Relevance
“…This is not surprising, given the fact that the medical variables were assessed rather roughly and because it was too short after termination of treatment to find late effects of treatment. The limited impact of medical variables on HRQoL has been found in many studies among survivors of childhood cancer [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, given the fact that the medical variables were assessed rather roughly and because it was too short after termination of treatment to find late effects of treatment. The limited impact of medical variables on HRQoL has been found in many studies among survivors of childhood cancer [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The enormous increase in survival [4][5][6][7][8] has heightened the need to investigate the consequences of childhood cancer. An increasing number of studies have been directed at assessing Health Related Quality of Life (HRQoL) in long-term survivors, and considerable literature has been devoted to the pediatric patients and their parents during cancer treatment [1,9,10]. Less is known about what happens in the first few years after treatment in the run-up to long-term survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors. Finally, a few studies have found that the prevalence of depression in survivors of childhood cancer equal that of healthy controls (Gray et al, 1992;Zebrack and Zeltzer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They are confronted with a life-threatening disease mostly implying extensive treatment with negative side-effects and the risk of negative long-term consequences. Considerable literature has been devoted to the long-term adjustment of the child [2][3][4]. It can be concluded that dealing with childhood cancer is a dramatic event that could influence physical and psychosocial functioning long time after termination of the treatment [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, post-traumatic stress symptoms appeared to be common in families of childhood cancer; among survivors of childhood cancer, as well as among their parents [7][8][9][10]. Nevertheless, many long-term survivors of childhood cancer turned out to function well [11,12](see reviews by Langeveld et al [3] and Stam et al [4]). This appeared also to be true for their parents; overall, most of them did not experience more emotional disturbances than healthy controls [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%